Processes of revitalization and preservation of urban districts: the case of Vila Belga, Santa Maria, Rio Grande do Sul, Brazil - Scortegagna Socal, Ana Julia (2024)
The article reviews the transformations undergone by the railway architectural complex of Vila Belga, in Santa Maria, Rio Grande do Sul, from the decadence caused by the end of railway transport in the 1990s, the listing of the architectural complex, to the transformation into the current construction project. revitalization called Centro-Gare Creative District. The methodology used was bibliographic and documentary research, on-site visits and analysis of photographs in different historical periods, taking as a time frame the period from 1997 to 2023, encompassing different times in which transformations occurred in Vila Belga. It was observed that the three initiatives identified and analyzed involved both the public authorities and the community itself, which strengthens the actions carried out and contributes to their continuity.